PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GORVERNANCE TERHADAP NILAI PERUSAHAAN MENGGUNAKAN ROA SEBAGAI VARIABEL INTERVENING - Tri Puji Rahayu; Titiek Suwarti (STEKOM PRESS, 2023)
This study aims to examine the effect of intellectual capital and good corporate governance on firm value using ROA as an intervening variable. This study used a purposive sampling method in selecting the sample. The research data used in secondary data obtained from goods and consumption companies that have gone public and are listed on the Indonesia Stock Exchange (IDX) in 2016-2021. the independent variables used in this study are intellectual capital and GCG in the form of institutional share ownership and independent board of commissioners. And dependent variable is firm value and intervening variable used in this study is profitability. Profitability is able to mediate Intellectual Capital, Independent Board of Commissioners, Institutional Ownership on Company Value.